Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Dosen Dalam Proses Belajar Mengajar Program Studi DIV Bidan Pendidik Di STIKes Husada Borneo Banjarbaru - Ni Wayan Kurnia Widya Wati; Ahmad Suriansyah; Muhammad Rustam Effendi (Jurnal Kesehatan Indonesia, 2017)
The quality of educational institutions is influencedby the inputs to the education system which is including the students, faculty and supporting facilities or infrastructures in teaching and learning process. These three factors are related and influenced each other in order to create a successful learning process. This research is a quantitative research which is included cross sectional study. Population in this study took the all of lecturers in Midwife Educator Study Program in STIKes Husada Borneo Banjarbaru as many as 40 people that using total sampling technique. The Instrument on this study used the questionnaire were then tested its validity with Pearson Product Moment correlation technique, while the reliability testing using the formula of Cronbach's alpha. The data analysis technique used to find the relationship both of them is the chi-square test, whereas to know the influence of them is used regressing.The results of the research shown that there is a positive and significant correlation between age, education, motivation, job satisfaction, perception of rewards to performance of lecturer DIV Midwife Educator Study Program, there is the influence of age, education, motivation, satisfaction, perception of reward collaborate with the performance of Lecturer in Midwife Educator Study Program STIKes Husada Borneo in the teaching-learning process. Based on the results of research, it can be suggested to the lecturers of DIV midwife educators to become self-evaluation materials, in order to cultivate and improve the basic tasks of lecturers, especially in implementing the learning process